Morning Routines as a Discipline-Oriented Character Education Mechanism in an Islamic Boarding Junior High School - Nisa, Fadhilatun; Rena, Syahidah; Al-Ghifary, Muh Ubaydillah (DAYAH: Journal of Islamic Education, 2025)
This study aims to examine morning routine activities as a discipline-oriented character education mechanism at SMP Islam Al-Falah Rempoa Boarding School, South Tangerang. The research employed a qualitative descriptive case study approach, with data collected through observations, semi-structured interviews, and document analysis involving the school principal, vice principal for student affairs, vice principal for curriculum, Islamic Religious Education (PAI) teachers, duty teachers, and students. The findings indicate that morning routines are planned collaboratively, implemented through structured time–place arrangements and role distribution, and framed within an Islamic educational orientation. Consistent implementation is associated with discipline-related behaviors reflected in students’ rule compliance, punctuality, learning readiness, and responsibility in completing tasks, across both school and dormitory contexts as described in this study. However, student engagement varies, particularly in activities perceived as less interesting, suggesting the importance of routine refinement through activity variation and student-involving formats to strengthen intrinsic motivation. The study concludes that morning routines can function as an effective instrument of character education when systematically designed and supported by school stakeholders, while continuous evaluation is needed to address engagement differences. Abstrak Penelitian ini bertujuan menganalisis morning routine sebagai mekanisme pendidikan karakter berorientasi disiplin di SMP Islam Al-Falah Rempoa Boarding School, Tangerang Selatan. Penelitian menggunakan pendekatan studi kasus deskriptif kualitatif, dengan pengumpulan data melalui observasi, wawancara semi-terstruktur, dan analisis dokumen yang melibatkan kepala sekolah, wakil kepala sekolah bidang kesiswaan, wakil kepala sekolah bidang kurikulum, guru Pendidikan Agama Islam (PAI), guru piket, serta siswa. Hasil penelitian menunjukkan bahwa morning routine direncanakan secara kolaboratif, dilaksanakan melalui pengaturan waktu–tempat yang terstruktur dan pembagian peran, serta dipahami dalam bingkai orientasi pendidikan Islam. Implementasi yang konsisten berkaitan dengan perilaku disiplin yang tercermin pada kepatuhan terhadap aturan, ketepatan waktu, kesiapan belajar, dan tanggung jawab dalam penyelesaian tugas, baik di lingkungan sekolah maupun di lingkungan asrama. Namun demikian, partisipasi siswa masih bervariasi, terutama pada kegiatan yang kurang diminati, sehingga diperlukan penyempurnaan rutinitas melalui variasi aktivitas dan format yang lebih melibatkan siswa untuk memperkuat motivasi intrinsik. Secara keseluruhan, morning routine dapat menjadi instrumen pendidikan karakter yang efektif apabila dirancang secara sistematis dan didukung oleh warga sekolah, disertai evaluasi berkelanjutan untuk mengatasi perbedaan keterlibatan siswa.